Perancangan Sistem Pendukung Keputusan Penerimaan Siswa Baru Dengan Menerapkan Metode VIKOR - Azmi, Dinda Tamara; Barus, Handayani; Marbun, Fika Liana; Ginting, Garuda; Hasibuan, Nelly Astuti (JURIKOM (Jurnal Riset Komputer), 2018)
In the registration of new students have requirements, such as new student data, birth certificate, family card, age, intelligence, graduation, which is usually still manually recorded data so that it is considered less effective Because of that, the author is interested in creating an application that can help either the school or the students to make it easier in processing new student enrollment. Decision Support System is a computerized system and designed to increase the effectiveness of decision making to solve problems that are semi-structured and unstructured so that in the process of making decisions can be more qualified. This application will be made is an application that guided by VIKOR method. Therefore, applications based on VIKOR method is considered suitable for calculating the best skin types for shoemaking